Modification of boundary structure and magnetic properties of Nd-Fe-B sintered magnets by diffusing Al/Cu co-added alloy ribbons. (February 2019) - Lu, Kechao; Bao, Xiaoqian; Chen, Guixian; Zhang, Xuejiao; Tang, Minghui; Mu, Xing; Li, Jiheng; Gao, Xuexu
Abstract: Wetting experiments of Tb70 Cu30, Pr52.5 Tb17.5 Cu30, Pr60 Tb20 Al20 and Pr60 Tb10 Cu15 Al15 (at.%) ingots over Nd-Fe-B sintered magnet were carried out and suggested that alloys containing Al possessed better wettability and mobility. Interfacial analysis suggested that at interface between Pr60 Tb20 Al20 and magnet, Tb mainly diffused along grain boundaries without abnormal Tb-rich grains, which were observed in the systems of Cu-added ingots. On the basis of these, grain boundary diffusion with alloy ribbons was applied and coercivity increment of over 11 kOe was achieved by consuming below 0.5 wt.% Tb in diffused magnet by Pr60 Tb10 Cu15 Al15, which was mainly attributed to homogeneous and thin Tb-rich shells. Graphical abstract: